Georgia in Transition : Perspectives on the Europeanization of Higher Music Education - Kekenadze Gustafsson, Iveri ; 0009-0005-8109-8103; Sharikadze, Nana (Proceedings of the International Society for Music Education : 36th World Conference on Music Education, 2024)
Music and Performing Arts is one of the fields Georgia can pride itself on internationally. While the country is in transition as it officially embarks on its long path to the European Union membership, this study explores the process of Europeanization of Higher Music Education in Georgia. Authors analyze how Higher Music Educational Institutions employ European projects for organizational change at a grassroots level and to what extent and in what way supranational and national policy instruments influence the outcome at the local—institutional level. This study categorizes Georgia's Higher Music Education sector into three major stages since the country restored independence in 1991 and uses structural, institutional, and organizational approaches for collected data analysis. The findings suggest that significant challenges remain despite emerging European support in the cultural area and active cooperation between major stakeholders in the sector and their European counterparts.